General election 15: the star's facebook news agenda and how it influences first-time Malaysian voters - Ng, Kah Kei (2024)

(untitled)
General Election-15 (GE-15) has brought about a significant change for Malaysia. First-time Malaysian voters have emerged as a major influence in this political shift. Simultaneously, social media, particularly Facebook, has played a pivotal role in shaping the news frame and enabling every citizen to access the latest information, issues, and crises. Additionally, the voting behaviour of first-time Malaysian voters has become a significant area of research during GE-15. The objective of this study is to identify the news frame set by The Star’s Facebook during GE-15 and to examine how Facebook news influences the voting behaviour of first-time Malaysian voters. This research employs two quantitative approaches: content analysis to investigate how The Star’s Facebook Page set the news frame, and the distribution of a survey questionnaire to 100 first-time Malaysian voters from the Klang Valley region who participated in GE-15. The findings of the research indicate that The Star’s Facebook Page featured 12 categories among 237 news articles during the GE-15 campaign period. Furthermore, the study concludes that The Star’s Facebook news has indeed influenced the voting behaviour of first-time Malaysian voters, and the main reason is the news from The Star’s Facebook is informative.